Influencia de la Funcionalidad Familiar en la Motivación Académica en Jóvenes de una universidad privada de Arequipa - Ortega López, Camila Natalia (2025)
The present research aimed to analyze the influence of family functioning on academic motivation in students at a private university in Arequipa. A quantitative study was conducted with a non-experimental, predictive design. A sample of 435 university students from 12 professional programs, aged between 18 and 26 years, was used. 54.9% were female and 45.1% were male. The Family Adaptability and Cohesion Evaluation Scale (FACES III) and the Educational Motivation Scale (EME) were administered to students. It was found that family functioning has no influence on academic motivation in university students. It was also found that 44.4% perceived their family as flexible, 40% perceived a connected family, 55.6% perceived a balanced family, and 70.6% of the sample had high motivation. Finally, the variables were compared according to age and sex, finding that the perception of adaptability within the family is greater in students between 23 and 26 years old and is higher in men than in women. Likewise, in the cohesion dimension and the motivation variable, no significant differences are seen according to age and sex.